UNSUR DRAMATIK DALAM NASKAH RANDAI SAGAN BADAYUANG HANYUIK SARANTAU VERSI SANGGAR RANAH TIGO RASO (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to analyze the dramatic elements in the Randai script 'Sagan Badayuang Hanyuik Sarantau' version by Sanggar Ranah Tigo Raso. The study uses a qualitative approach with content analysis method. The research instrument is the researcher themselves, assisted by stationery and a camera. Data was collected through literature study and classification. The steps to analyze include data collection, data reduction, data presentation, and drawing conclusions. The results show that the 'Sagan Badayuang Hanyuik Sarantau' script has several story-building elements, namely Theme, Characters and Characterization, Plot, Setting, and Message. The theme contained is the social life of the Minangkabau community that upholds customs and family values. The character Sumarak Alam is portrayed as brave, wise, loyal, humble, polite, and courteous. The character Mayang Taurai is religious, caring, and keeps her feelings to herself polite, and courteous. The character Datuak Rajo Mangkuto is religious, caring, loving, wise, and firm. The character Rajo Batuang is cunning, arrogant, aggressive, vengeful, emotional, and reckless. The character Panyariang Awan is a provocateur, rough, and harsh. The setting is in the Minangkabau land of West Sumatra. The message contains moral, social, and religious values. This script has a five-stage plot: Exposition, the background of the Sumarak Alam uncle-nephew relationship, Datuak Rajo Mangkuto, and Mayang Taurai. Complication, Panyariang Awan tells Rajo Batuang about Sumarak Alam coming to see Mayang Taurai, which angers Rajo Batuang. Climax, a nighttime meeting between Rajo Batuang, Panyariang Awan, Sumarak Alam, and Mayang Taurai sparks a fight. Resolution, Mayang Taurai explains that Sumarak Alam is her father's nephew who just returned from traveling. Conclusion, Sumarak Alam chooses to make peace according to Minangkabau customs, and all the characters make amends.